Combining techniques of weak signals in the bistable parallel array system. Issue 9 (4th May 2018) - Liang, Linlin; Huang, Haiyan; Zhang, Nina; Wang, Danyang; Liu, Jin; Li, Zan
Abstract : Bistable parallel array system can efficiently improve the signal‐to‐noise ratio (SNR) gain and further significantly lower bit‐error‐rate (BER) when the SNR is low. The bistable parallel array system is widely studied due to its outstanding advantages. This study presents a new method that applies combining techniques including maximum ratio combining (MRC), equal gain combining (EGC), and selection combining (SC) to the bistable parallel array system, and derives the formulas of the SNR gain, energy efficiency, and numerically calculates the BER. Through comparative analysis of these three combining techniques, it demonstrates the BER performance of the EGC technique in bistable parallel array system slightly inferiors to MRC, and the worst is SC. While the performance of all these three kinds of combining techniques is better than that of the single branch case. Importantly, higher SNR gain, higher EE and lower BER can be obtained in non‐Gaussian noise cases than that in Gaussian noise cases.